Association of the IceCube neutrinos with blazars in the CGRaBS sample - Kouch, Pouya M.; Lindfors, Elina; Hovatta, Talvikki; Liodakis, Ioannis; Koljonen, Karri I. I.; Nilsson, Kari; Kiehlmann, Sebastian; Max-Moerbeck, Walter; Readhead, Anthony C. S.; Reeves, Rodrigo A.; Pearson, Timothy J.; Jormanainen, Jenni; et al. (EDP Sciences, 2025)
The origin of high-energy (HE) astrophysical neutrinos has remained an elusive hot topic in the field of HE astrophysics for the past decade. Apart from a handful of individual associations, the vast majority of HE neutrinos arise from unknown sources. While there are theoretically motivated candidate populations, such as blazars – a subclass of active galactic nuclei with jets pointed toward our line of sight – they have not been convincingly linked to HE neutrino production yet. Here, we perform a spatio-temporal association analysis between a sample of blazars (from the CGRaBS catalog) in the radio and optical bands and the most up-to-date IceCube HE neutrino catalog. We find that if the IceCube error regions are enlarged by 1◦ in quadrature, to account for unknown systematic errors at a maximal level, a spatio-temporal correlation between the multiwavelength light curves of the CGRaBS blazars and the IceCube HE neutrinos is hinted at, least at a 2.17σ significance level. On the other hand, when the IceCube error regions are taken as their published values, we do not find any significant correlations. A discrepancy in the blazar-neutrino correlation strengths, when using such minimal and enlarged error region scenarios, was also obtained in a recent study by the IceCube collaboration. In our study, this difference arises because several flaring blazars – coinciding with a neutrino arrival time – happen to narrowly miss the published 90%-likelihood error region of the nearest neutrino event. For all of the associations driving our most significant correlations, the flaring blazar is much less than 1◦ away from the published error regions. Therefore, our results indicate that the question of the blazar-neutrino connection is highly sensitive to the reconstruction of the neutrino error regions, whose reliability is expected to improve with the next generation of neutrino observatories.